2015
DOI: 10.1155/2015/672164
|View full text |Cite
|
Sign up to set email alerts
|

Acute Popliteal Artery Occlusion after Revision Total Knee Arthroplasty

Abstract: Acute arterial occlusions are a rare complication of total knee arthroplasty (TKA). However, in revision TKA, the risk of such complications is higher and these complications can lead to amputation if not adequately treated. We describe a case of acute popliteal artery occlusion 4 hours after second revision TKA in a patient with a history of several surgical procedures because of periprosthetic infection at a previous hospital. Revascularization was achieved via bypass grafting and amputation was narrowly avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…[ 10 ] An alternative cause of arterial vasospasm is arterial compression by surrounding soft tissue from manual manipulation during surgery which has been reported to cause acute arterial occlusion. [ 6 ] During the case highlighted in this report, there was no significant bleeding that would suggest direct injury to the popliteal artery when the tourniquet was taken down intra-operatively. Additionally, the vascular surgeon did not note any obvious direct injury to the popliteal artery.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…[ 10 ] An alternative cause of arterial vasospasm is arterial compression by surrounding soft tissue from manual manipulation during surgery which has been reported to cause acute arterial occlusion. [ 6 ] During the case highlighted in this report, there was no significant bleeding that would suggest direct injury to the popliteal artery when the tourniquet was taken down intra-operatively. Additionally, the vascular surgeon did not note any obvious direct injury to the popliteal artery.…”
Section: Discussionmentioning
confidence: 86%
“…Tsujimoto et al observed an acute popliteal artery occlusion in an 83-year-old male following revision TKA. [ 6 ] Inomata et al describe an acute arterial occlusion after bilateral TKAs in an 80-year-old Asian female. [ 7 ] Ohira et al described an acute popliteal thrombus in a 71-year-old male with calcium pyrophosphate dihydrate crystal deposition disease.…”
Section: Discussionmentioning
confidence: 99%
“…After careful search and screening, 36 studies with 47 cases of arterial occlusion after knee arthroplasty in the past 35 years (1984–2018) were included in the analysis (1 from the present study) (Table S1). Demographics, predisposing conditions, perioperative details, arterial occlusion information, and prognosis are shown in Tables .…”
Section: Resultsmentioning
confidence: 99%
“…Early arterial problems after TKA can be treated by open thrombectomy, bypass surgery, or endovascular methods. [17][18][19] Chang et al [20] reported preoperative DVT incidence as 2.6% per patient and 1.6% per knee by computed tomography/indirect venography. Preoperative prevalence and postoperative incidence of major DVT were reported as 2.5%.…”
Section: Discussionmentioning
confidence: 99%